Evaluation of constitutional chromosomal abnormalities: experience of a tertiary healthcare diagnostic laboratory in India - Salaskar, Vidya; Pradhan, Gauri; Pais, Anurita; Kadam, Chaitali; Matkar, Sunmeet (International Journal of Research in Medical Sciences, 2017)
Background: Structural and numerical chromosomal aberrations contribute significantly to genetic disease. Unbalanced aberrations are associated with congenital anomalies, mental retardation and underdevelopment of secondary sexual characters while balanced structural chromosomal abnormalities contribute to an increased risk for infertility, bad obstetric history and chromosomally unbalanced offspring with multiple congenital abnormalities and intellectual impairment. Aim of the current study was to determine the prevalence and characterization of cytogenetic aberrations in 8445 cases referred during the years 2010-2013 for cytogenetic evaluation. Methods: Metaphase chromosomes from 72-hour blood lymphocyte culture were prepared for Giemsa-Trypsin-G banding. Characterization of marker chromosomes were done by M-FISH and subtle chromosomal aberrations were evaluated by targeted FISH using centromeric probes for chromosome 13,18,21, X and Y and loci specific probes for microdeletion syndromes and SRY gene. Results: Variant forms of trisomies i.e. partial trisomies were seen in cases with Edwards and Patau syndrome. Sex chromosomal abnormalities associated with puberty and reproductive problems were seen in cases with Turner syndrome, Klinefelter syndrome and also in females with primary amenorrhea. Autosomal reciprocal translocations were the most common chromosomal changes in couples with recurrent abortions. In order to increase the diagnostic yield and evaluate variations, FISH and m-FISH were additional tests done to characterize the genetic variations. Conclusions: Along with Karyotyping SRY, XIST, SHOX9 gene analysis and Y microdeletion analysis are also critial tests to assess the possibilities for normal development or assisted reproduction in individuals with sex chromosomal abnormalities.